Co-immunizing with HMGB1 enhances anti-tumor immunity of B7H3 vaccine in renal carcinoma. (November 2021) - Sun, Huanyou; Li, Juan; Hu, Wenwen; Yan, Yinan; Guo, Zengli; Zhang, Zichun; Chen, Yuxin; Yao, Xuefan; Teng, Ling; Wang, Xinyuan; Li, Liantao; Chai, Dafei; et al.
Highlights: H1-pHMGB1/pB7H3 vaccine enhanced the induction and mature of DCs. H1-pHMGB1/pB7H3 could induce tumor-specific CD8 + T cell responses. H1-pHMGB1/pB7H3 vaccine could inhibit the tumor growth of renal cancer. CD8 + T cells are required for the induction of protective anti-tumor immunity by H1-pHMGB1/pB7H3. Abstract: Metastatic renal carcinoma is a kind of tumor with high degree of malignancy, but there are no effective treatment methods and strategies at present. In this study, we designed a folate-grafted PEI600-CyD (H1) nanoparticle-mediated DNA vaccine containing an adjuvant of high mobility group box 1 protein (HMGB1) and a tumor-specific antigen of B7H3 (CD276) for renal carcinoma therapy. Mice bearing subcutaneous human B7H3 (hB7H3)-Renca tumor were immunized with H1-pHMGB1/pB7H3, H1-pB7H3, H1-pHMGB1, or Mock vaccine. Compared to other control groups, the growth of the tumor was significantly inhibited in H1-pHMGB1/pB7H3 vaccine group. The increased proportion and mature of CD11c + DCs were observed in the spleen of H1-pHMGB1/pB7H3 treated mice. Likewise, HMGB1 promoted B7H3 vaccine to induce tumor-specific CD8 + T cell proliferation and CTL responses. Beyond that, H1-pHMGB1/pB7H3 vaccine strengthened the induction of functional CD8 + T cells. With the depletion of CD8 + T cells, the anti-tumor effect of H1-pHMGB1/pB7H3 also disappeared, indicating that CD8 + T cells are the key factor of the anti-tumor activity of the vaccine. So, to sum up, H1-pHMGB1/pB7H3 vaccine could achieve the desired anti-tumor effect by enhancing the response of tumor-specific functional CD8 + T cell responses. H1 nanoparticle-based vaccines may have great potential and prospect in the treatment of primary solid tumors.